Aspectos clínicos e genéticos, avaliação cognitiva e neuroimagem em pacientes com Ataxia autossômica recessiva relacionada ao gene SYNE1 - Gama, Maria Thereza Drumond [UNIFESP] (2019)
BACKGROUND: Cerebellar ataxias are a heterogenous group of diseases that can affect individuals of all ages and are characterized by degeneration of the cerebellum and cerebellar pathways. The most common genetic forms of ataxias are those caused by abnormal expansion of trinucleotides, whose genetic tests are already widely used. With the advancement of diagnostic techniques, many genes could be identified as causing undetermined ataxias, as the case of ataxia related to the mutation of the SYNE1 gene, wich was first described in 2007 in a Canadian population. OBJECTIVES: In order to adress different objectives this clinical protocol is divided into sub-studies as follows: Study 1– to asses clinically and genetically diagnosed patients with ataxia related to SYNE1 in the Brazilian population.Study 2– to perform a neuropsychological and psychiatric analysis in these patients. Study 3– to perform multimodal neuroimaging analyses and investigate cerebelar and potential extra-cerebellar changes in SYNE1 ataxia. METHODOLOGY: Patients aged 10 to 40 years with cerebellar ataxia and retained reflexes were selected. The clinical protocol consisted of: clinical evaluation, ataxia scales (ICARS e SARA), molecular test, neuropsychological and specific psychiatric analyses and multimodal neuroimaging protocol. Specific statistical analysis is described in each study separately. RESULTS: Study 1: it was found a frequency of 10.25% of the disease in this sample of patients and the clinical phenotype varied from the classical cerebellar form to the complex forms, wich has association with motor neuron disease. Study 2 - the following domains of cognition were altered: executive function, attention and processing speed. In psychiatric analyses, a mild degree of anxiety and difficulty in the abstraction of thought was observed. Study 3 – it was found a cerebellar involvement (cortical atrophy and alteration of the white matter), reduction of cortical thickness in the primary motor area and pre-motor area and degeneration of the cortico-spinal tract in the motor cortex, internal capsule and cerebral peduncle, similar findings to those found in motor neuron disease. CONCLUSION: This study was the first to demonstrate the frequency of cerebellar ataxia related to the mutation of the SYNE1 gene in the Brazilian population. The phenotypic variability was confirmed, as was described in other international studies. Some cognitive domains were involved, wich corroborates the role of the cerebellum in cognition. The neuroimaging findings were consistent with the clinical heterogeneity described.